Exploring the impacts of natural elements on relieving psychological stress in restorative virtual environments - Han, Yuqing (Edelweiss Applied Science and Technology, 2025)
With rising stress levels in modern society, restorative virtual environments (RVEs) offer promising solutions for promoting emotional well-being through immersive, nature-inspired design. However, limited research has examined which specific natural elements within RVEs most effectively alleviate psychological stress. This study involves a controlled experiment conducted within Rec Room, a virtual reality platform, to examine how both fixed green environments and natural, moving elements affect users' emotional states and physiological responses. Four indoor VR conditions were developed, manipulating the presence of plants and dynamic elements such as light shifts and wind-driven motion. Although biometric indicators showed limited differences, qualitative data revealed a clear preference for environments that mimicked natural growth patterns and incorporated familiar, calming features. Participants associated these spaces with past positive experiences, indicating that perceived realism and emotional resonance play important roles in stress recovery. Based on these findings, we propose three design principles for restorative VR environments: preserve natural forms, favor organic interactions, and anchor design in users' lived memories.